What factors contribute to the unemployment duration of youth: A case study of the Action Volunteers Africas youth labour market programme - Setlhodi, Mapaseka (School of Economics, 2020)
The incidence of unemployment falls most harshly on youth, who are generally low skilled and often have no experience of formal sector employment; with just 24.4 percent of young people being active in the labour market. In an attempt to assist this disenfranchised so called ‘lost generation’ there has been a major shift from passive to active labour market programmes in many countries across the world in support of the unemployed, where these programmes often concentrate on the youth. But the results on these active labour market interventions are very mixed, in terms of their effectiveness, with some countries having experienced significant improvements in unemployment levels; and others are yet to bring to fruition the economic benefits the programmes had hoped to achieve. Through the use of a qualitative research method approach, by means of surveys, this paper aims to lend to the lessons around youth labour market interventions by conducting a case study on a particular NGO’s youth intervention program to see if it has had any impact on reducing youth unemployment. What sets the programme apart is that it offered meaningful volunteering as a form of work experience as well as a self-development component which allows the youth to be more self-aware. The study found that overall the time youth spend in unemployment after completing the programme decreased by 6 months and that other unemployment duration determining factors play a key role in determining how long a youth spends in unemployment. The study found that the attitudes of the participants changed to a more positive outlook on their future prospects once they have completed the program; which lends itself to have a positive impact on job search activity.